1981
DOI: 10.1210/endo-108-4-1148
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Gonadotropin-Releasing Hormone (GnRH) Receptors: Characterization, Distribution, and Induction by GnRH*

Abstract: Gonadotropin-releasing hormone (GnRH) and its analogs have direct extrapituitary effects on the gonads to inhibit steroidogenesis. In the present study, the nondegradable GnRH analog [ 125 I]D-Ala a -des-Glyio-GnRH ethylamide is shown to specifically bind to ovarian, testicular, and adrenal membrane preparations. The ovarian GnRH receptor has a binding affinity similar to that of the anterior pituitary receptor and is specific for GnRH and GnRH analogs.The GnRH-binding capacity of whole ovarian membrane prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(51 citation statements)
references
References 34 publications
4
46
0
1
Order By: Relevance
“…The first evidence for the presence of ovarian GNRHR, through ligand-specific binding sites, was observed in rat granulosa and luteal cells (Reeves et al 1980, Pieper et al 1981, Olofsson et al 1995. Subsequently, the presence of GNRHR mRNA was also identified in human granulosa luteal cells (Kang et al 2000) and in both follicles and CL of bovine ovary (Ramakrishnappa et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence for the presence of ovarian GNRHR, through ligand-specific binding sites, was observed in rat granulosa and luteal cells (Reeves et al 1980, Pieper et al 1981, Olofsson et al 1995. Subsequently, the presence of GNRHR mRNA was also identified in human granulosa luteal cells (Kang et al 2000) and in both follicles and CL of bovine ovary (Ramakrishnappa et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This fact shows the participation of the peripheral nervous system in ovarian function (Condon & Black 1976, Coleman et al 1979, Harwood et al 1980, Adashi & Hsueh 1981, Aguado et al 1982, Aguado & Ojeda 1984a,b, Norjavaara et al 1984, Sosa et al 2000. Furthermore, some neurotransmitters that stimulate ovarian progesterone release such as noradrenaline and vasoactive intestinal peptide (Ojeda & Aguado 1985, Dees et al 1986, Ojeda & Lara 1989, Dissen et al 1993, Gerendai et al 1995, Kalekzyc et al1995, or peptides with inhibitory effects such as gonadotrophinreleasing hormone (Hsueh & Erickson 1979, Huesh & Jones 1981, Pieper et al 1981, Sheela Rani et al 1983) and gamma aminobutyric acid (Erdö et al 1985, Häppölä et al 1987 have been found in the ovary. Some of them are also present in the SON and the coeliac ganglion (Jan & Jan 1981, 1982, 1983, Sejnowski 1982, Dalsgaard et al 1983, Karhula et al 1988, Lascar et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Since follicular tissue has been reported to contain higher concentrations of LHRH receptors than luteal tissue (Pieper, Richards & Marshall, 1981) …”
Section: Resultsmentioning
confidence: 99%